PERANCANGAN KEMASAN COKLAT CHOKATO KELURAHAN KAPALO KOTO, KOTA PAYAKUMBUH - NANDA MULYADI, Drs. Syafwandi, M.Sn., Drs. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
The company of Chokato chocolate in Kapalo Koto Urban Vilage. The packaging of Chokato’s chocolate is one of the chocolate producer in Payakumbuh, which is located in Kapalo Koto Urban Village, Aur Kuning, South Payakumbuh, Payakumbuh City. Established in 2006 and led by Mr. Joni Saputra.Design method is design of Chokato’s chocolate in Kapalo Koto constituted by chocolate packaging products Chokato in Kapalo Koto Urban Village which has a distintctive scent and flavor, and design brands that will be applied to the packaging. The data analysis method which is used is the SWOT analysis, because in this case the writer designning packaging that is based on the strength of products from chocolate company Chokato in the Urban village of Kapalo Koto and also with the consideration of weakness, opportunities and threats that a comparison between the packaging of chocolate Chokato Urban Village Kapalo Koto with competitors.The design of the brand and packaging concept taken from chocolate products Chokato Kapalo Koto Urban Village which has a distinctive scent and flavor and the brand is based on the concept of incorporation of the letters shaped cocoa fruit.The media support used in the design of Chokato’s chocolate in the Kapalo Koto Urban Village including cards, paper bag, stamp, sticker, clothes, g;asses, key chains and poster.Key Word : Design, Chocolate, Brand, Package